USING ‘BRAINSTORMING’ TECHNIQUE TO IMPROVE STUDENTS’ ABILITY IN WRITING ESSAYS - Eliwarti (English Study Program University of Pasir Pengaraian, 2016)
This research aims to improve students‟ ability in writing essays. “Listing” technique in Brainstorming activity was applied to students taking Writing III subject. Before and after the action, a pre-test and a posttest were conducted. After the action (two cycles), there was an increase of the mean score from the pre-test (53.77) to posttest (63.49). The result of observation also showed that the students‟ activity in following Listing technique is 68.6%. This fulfilled the criteria applied (³ 61). Besides, t-test was also used to see the effectiveness of the Listing technique. The result showed that „t‟ observed (3.92) is greater than „t‟ table at the level of 0.05 (2.021) and 0.01 (2.704) This indicates that Listing technique is effective in improving the students‟ ability in writing essays.